HOW TO TRAIN YOUR DRAGON - Vijaya; Rao (Kuala Lumpur Mind to Mind, 2005)
is a captivating children's story that revolves around an unusual friendship between a horse and a lion. In the tale, the horse and the lion form an alliance and work together to face various challenges and adventures. Their collaboration highlights themes of mutual respect, teamwork, and the idea that true strength lies in unity and cooperation. The story emphasizes how different beings, despite their differences, can achieve great things when they support and understand each other. It is designed to engage young readers with its entertaining plot and valuable lessons about friendship and working together.